PENERAPAN PERTANGGUNG JAWABAN KOMANDO DI INDONESIA ATAS PELANGGARAN HAM BERAT KATEGORI KEJAHATAN TERHADAP KEMANUSIAAN - Joko Setiyono (Masalah-Masalah Hukum, 2010)
The legal attempt enforcing law against the gross violation of human right based on the commander responsibility principle, is not only a domestic concern of nation but it already became an international concern, in order to cut loose the chain impunity practice. The effort to prosecuted and to put on thai for military leaders, the chief of police officer and other civilian leaders, for the gross violation of human rights in Indonesia is a very serious legal problem which can not be pull to be aside and is the mian concern in this research